Safety of the patient in an emergency situation: perceptions of the nursing team - Andréa Tayse de Lima Gomes; Marcos Antônio Ferreira Jr; Pétala Tuani Candido Oliveira Salvador; Manacés dos Santos Bezerril; Flávia Barreto Tavares Chiavone; Viviane Euzébia Pereira Santos
ABSTRACT Objective: To know the perception of nursing professionals about the essential aspects to provide safe care to polytraumatized patients in emergency services. Method: Descriptive and mixed study, performed with a focus group and projective techniques. The sample was made of seven nursing professionals. Data analysis took place through the Interface de R pour Analyses Multidimensionnelles de Textes et de Questionneires and SPSS 22.0 softwares. Results: Based on the analysis of participants' speeches, three content partitions emerged in the Descending Hierarchical Classification. 1) Structure: need for changes; 2) The process: safe actions by the nursing team; and 3) Care free from damage as the sought result. Conclusion: Patient safety in emergency situations must rely on a proper environment and an organized sector, good conditions to transport patients, use of routines and protocols, identification and organization of the beds.